2023
DOI: 10.1001/jamapediatrics.2023.4499
|View full text |Cite
|
Sign up to set email alerts
|

Newborn and Early Infant Outcomes Following Maternal COVID-19 Vaccination During Pregnancy

Sarah C. J. Jorgensen,
Samantha S. M. Drover,
Deshayne B. Fell
et al.

Abstract: ImportanceThe study team previously showed that maternal mRNA COVID-19 vaccination during pregnancy confers protection against SARS-CoV-2 infection and COVID-19–related hospital admission in newborns and young infants. In this study, the study team evaluated newborn and early infant safety outcomes following maternal messenger RNA (mRNA) COVID-19 vaccination during pregnancy, for which there is limited comparative epidemiological evidence.ObjectiveTo determine if maternal mRNA COVID-19 vaccination during pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…This study had findings concordant with smaller studies and had the advantage of evaluating specific neonatal diagnoses that were selected a priori as having biologically plausible links to COVID-19 vaccination. It also included information on BMI in pregnant individuals, a potentially important 12 The Canadian study also reported that infants of vaccinated individuals had lower risk of severe neonatal morbidity, defined as a composite consisting of 7 neonatal procedures and 15 different diagnoses, including gestational age and birth weight. 12 Accordingly, the selective contributions of pregnancy outcomes and specific neonatal outcomes to the association with vaccination in pregnancy were unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This study had findings concordant with smaller studies and had the advantage of evaluating specific neonatal diagnoses that were selected a priori as having biologically plausible links to COVID-19 vaccination. It also included information on BMI in pregnant individuals, a potentially important 12 The Canadian study also reported that infants of vaccinated individuals had lower risk of severe neonatal morbidity, defined as a composite consisting of 7 neonatal procedures and 15 different diagnoses, including gestational age and birth weight. 12 Accordingly, the selective contributions of pregnancy outcomes and specific neonatal outcomes to the association with vaccination in pregnancy were unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that mRNA COVID-19 vaccination during pregnancy directly reduces neonatal mortality, although others have suggested that such a protective effect is biologically plausible. 12 The vaccine does not seem to pass the placenta or induce placental inflammation, and could not be traced in cord blood. 25,26 The current study's results could not elucidate the mechanisms that explain why infants of vaccinated individuals had lower risks of some outcomes including mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations